2016
DOI: 10.1007/s10548-016-0481-7
|View full text |Cite
|
Sign up to set email alerts
|

Detectability of Fast Ripples (>250 Hz) on the Scalp EEG: A Proof-of-Principle Study with Subdermal Electrodes

Abstract: To evaluate the possibility of detecting fast ripples (FRs) on the surface EEG of patients with focal pharmacoresistant epilepsy, and to investigate the relationship between scalp FRs and localization of the seizure onset zone (SOZ). We included 10 patients undergoing combined surface-intracranial EEG with ≥10 spikes in the surface EEG during the first 30 consecutive minutes of N3 sleep. FRs (≥4 consecutive oscillations above 250 Hz with an amplitude clearly exceeding that of the background) on the surface EEG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 39 publications
3
26
0
Order By: Relevance
“…67 Only very recently, the detection of HFOs > 250 Hz was attempted in a pilot study. 68 In this proof-of-principle study, it was shown that it might be feasible to record even frequencies > 250 Hz with scalp EEG; the rate of fast ripples was considerably lower than that of ripples. Table 1 provides an overview on the literature on HFO assessment in scalp EEG.…”
Section: Scalp Eegmentioning
confidence: 93%
“…67 Only very recently, the detection of HFOs > 250 Hz was attempted in a pilot study. 68 In this proof-of-principle study, it was shown that it might be feasible to record even frequencies > 250 Hz with scalp EEG; the rate of fast ripples was considerably lower than that of ripples. Table 1 provides an overview on the literature on HFO assessment in scalp EEG.…”
Section: Scalp Eegmentioning
confidence: 93%
“…[4][5][6][7] In contrast to ECoG, the identification of HFOs with noninvasive scalp electroencephalography (EEG) has proven more challenging. Although several studies have linked beta, gamma, and ripple activity to hypsarrhythmia 8 and epileptic spasms 9,10 in West syndrome, and to the seizure-onset zones in focal epilepsy, 11 it is only recently that fast ripples (FRs) have been identified with the use of subdermal scalp electrodes in adults with epilepsy, 12 and with the use of standard scalp electrodes in children with epilepsy. 13 Nevertheless, it has not yet been established that the visual identification and quantification of scalp HFOs is reliable.…”
mentioning
confidence: 99%
“…The recent demonstration that a custom low-noise amplifier increased FR-detection rates—and importantly—improved prediction of postoperative outcome is an encouraging development (Fedele et al, 2017). Further technological innovation is clearly needed, especially as it pertains to ongoing efforts to identify FR on scalp EEG (Pizzo et al, 2016). …”
Section: Discussionmentioning
confidence: 99%